2008
DOI: 10.1529/biophysj.107.109348
|View full text |Cite
|
Sign up to set email alerts
|

Putative Functions and Functional Efficiency of Ordered Cuticular Nanoarrays on Insect Wings

Abstract: The putative functions and functional efficiencies of periodic nanostructures on the surface of cicada wings have been investigated by atomic force microscopy (AFM) used as a tool for imaging, manipulation, and probing of adhesion. The structures consist of hexagonal close-packed protrusions with a lateral spacing of approximately 200 nm and may have multiple functionalities. Not only do the structures confer survival value by virtue of camouflage, but they may also serve as antiwetting and self-cleaning surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 35 publications
5
114
0
Order By: Relevance
“…The arrays consist of hexagonally packed spherically capped conical protuberances with a spacing and height of *200 nm and radius of curvature of *25-45 nm at the apex. Similar features have been found on the wings of a number of other cicada species including Aleeta curvicosta, Tamasa tristigma, Macrotristria angularis, Psaltoda claripennis and Thopha saccata (eg Watson et al 2008). The features are present on all areas of the dorsal and ventral wing membrane.…”
Section: Superhydrophobic Cuticlessupporting
confidence: 72%
See 4 more Smart Citations
“…The arrays consist of hexagonally packed spherically capped conical protuberances with a spacing and height of *200 nm and radius of curvature of *25-45 nm at the apex. Similar features have been found on the wings of a number of other cicada species including Aleeta curvicosta, Tamasa tristigma, Macrotristria angularis, Psaltoda claripennis and Thopha saccata (eg Watson et al 2008). The features are present on all areas of the dorsal and ventral wing membrane.…”
Section: Superhydrophobic Cuticlessupporting
confidence: 72%
“…A previous study has demonstrated the functional effectiveness of similar structures as an antireflective surface which presumably helps to camouflage the insect from predators (Watson et al 2008). The surfaces also demonstrated low adhesion with hydrophilic particles (Watson et al 2008). The multi-functional nature of the structures appears to be a common feature of the cuticle found on many insect species.…”
Section: Superhydrophobic Cuticlesmentioning
confidence: 96%
See 3 more Smart Citations